The Role of CEO Characteristics and Ownership Structure in Carbon Emission Disclosure: Evidence from Indonesian Listed Firms - Jaenette Annamelliadyla; Budi Chandra; Robby Krisyadi; Supriyanto Supriyanto; Surny Surny (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2025)
This study examines the effect of CEO characteristics foreign educational CEO and foreign ownership along with CEO Founder and CEO Age on carbon emission disclosure (CED) among firms listed on the Indonesia Stock Exchange from 2020 to 2023. Grounded in Upper Echelons Theory (UET), the study argues that observable attributes of top executives shape their cognitive perspectives and strategic preferences, thereby influencing environmental disclosure decisions. Using panel regression analysis on 1,623 firm-year observations from annual reports, sustainability reports, and ESGI data, the findings show that foreign educational CEO and CEO age have a positive and significant effect on carbon emission disclosure. In contrast, foreign ownership and CEO founder status do not exhibit significant effects in the main OLS models, while CEO founder shows a negative association in the GLS robustness test. These results suggest that individual CEO attributes play a more decisive role in shaping carbon disclosure practices than ownership structure. This study provides important implications for corporate governance, investors, and policymakers by highlighting the importance of executive characteristics in enhancing environmental transparency in emerging markets.